The Role of Pretreatment 18F-FDG PET/CT for Early Prediction of Neoadjuvant Chemotherapy Response in Patients with Locoregionally Advanced Nasopharyngeal Carcinoma - Yao J; Wang Y; Lin Y; Yang Y; Wan J; Gong X; Zhang F; Zhang W; Marks T; Wang S; Jin H; Shan H (Dove Medical Press, 2021)
Jijin Yao,1,2,* Ying Wang,3,* Yujing Lin,4 Yingying Yang,5 Jingjing Wan,3 Xiaohua Gong,1 Fanwei Zhang,3 Wangjian Zhang,6 Tia Marks,7 Siyang Wang,1 Hongjun Jin,2 Hong Shan2,8 1The Cancer Center of the Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of China; 2Guangdong Provincial Key Laboratory of Biomedical Imaging, The Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of China; 3Department of Nuclear Medicine, Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of China; 4Department of Pathology, The Fifth Affiliated Hospital of Sun Yat-sen University, Zhuhai, Guangdong Province, 519001, People's Republic of China; 5Department of Pharmacy, The Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of China; 6Department of Medical Statistics, School of Public Health, Sun Yat-sen University, Guangzhou, 510080, People's Republic of China; 7Department of Environmental Health Sciences, School of Public Health, University at Albany, State University of New York, Rensselaer, NY, 12144, USA; 8Department of Interventional Medicine, The Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of China*These authors contributed equally to this workCorrespondence: Hongjun JinGuangdong Provincial Key Laboratory of Biomedical Imaging, Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of ChinaEmail jinhj3@mail.sysu.edu.cnHong ShanDepartment of Interventional Medicine, Guangdong Provincial Key Laboratory of Biomedical Imaging, Fifth Affiliated Hospital, Sun Yat-sen University, Zhuhai, Guangdong Province, 519000, People's Republic of ChinaEmail shanhong@mail.sysu.edu.cnIntroduction: To evaluate the role of maximal standardized uptake values (SUVmax) and total lesion glycolysis (TLG) from serial 18F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) for early prediction of neoadjuvant chemotherapy (NAC) response in locoregionally advanced nasopharyngeal carcinoma (LANPC).Methods: A total of 121 LANPC patients who completed pretreatment 18F-FDG PET/CT between June 2017 and July 2020 were retrospectively included. The median age of all the participants was 50 years old (range: 19- 74 years), with 94 (77.7%) males and 27 (22.3%) females. The SUVmax from the primary tumor site (SUVmax-PT) and the total lesion glycolysis from the primary tumor site (TLG-PT) were recorded. Tumor response was calculated according to the Response Evaluation Criteria in Solid Tumor (RECIST) 1.1 Criteria at two-week post-secondary NAC cycle. Patients who achieved an objectively partial or full reaction after two cycles of NAC were defined as 'responders', and patients who obtained stability or progression were classified as 'non-responders'.Results: After two cycles of NAC, 96 patients were categorized as "responders" and 25 patients as "non-responders". The optimal thresholds of the SUVmax-PT were 11.8 and 38.5 for the TLG-PT. Non-responders were significantly associated with high SUVmax-PT (HR, 3.49; 95% CI, 1.17- 10.36; p = 0.024) and TLG-PT (HR, 4.45; 95% CI, 1.44- 13.78; p = 0.010) in multivariate analysis. Recursive partitioning analysis (RPA) categorized patients into three prognostic groups based on SUVmax-PT and TLG-PT: high-response group, intermediate-response group, and low-response group, with corresponding favorable response rates of 94%, 80%, and 55%, respectively. Moreover, a nomogram was created based on metabolic parameters that precisely projected an individual's response of NAC (C-index, 0.787; 95% CI, 0.533- 1.000).Conclusion: Pretreatment 18F-FDG PET/CT to measure SUVmax-PT and TLG-PT could be a useful non-invasive method for early indication of NAC efficacy. The nomogram based on PET/CT parameters may potentially provide direction for treatment decisions based on NAC levels.Keywords: nasopharyngeal carcinoma, neoadjuvant chemotherapy, tumor response, PET/CT, nomogram